CoOOH Nanosheets with High Mass Activity for Water Oxidation1. (10th June 2015) - Huang, Junheng; Chen, Junting; Yao, Tao; He, Jingfu; Jiang, Shan; Sun, Zhihu; Liu, Qinghua; Cheng, Weiren; Hu, Fengchun; Jiang, Yong; Pan, Zhiyun; Wei, Shiqiang
Abstract Endowing transition‐metal oxide electrocatalysts with high water oxidation activity is greatly desired for production of clean and sustainable chemical fuels. Here, we present an atomically thin cobalt oxyhydroxide (γ‐CoOOH) nanosheet as an efficient electrocatalyst for water oxidation. The 1.4 nm thick γ‐CoOOH nanosheet electrocatalyst can effectively oxidize water with extraordinarily large mass activities of 66.6 A g−1, 20 times higher than that of γ‐CoOOH bulk and 2.4 times higher than that of the benchmarking IrO2 electrocatalyst. Experimental characterizations and first‐principles calculations provide solid evidence to the half‐metallic nature of the as‐prepared nanosheets with local structure distortion of the surface CoO6−x octahedron. This greatly enhances the electrophilicity of H2O and facilitates the interfacial electron transfer between Co ions and adsorbed ‐OOH species to form O2, resulting in the high electrocatalytic activity of layered CoOOH for water oxidation.